Interspinous Spacer Implant in Patients with Lumbar Spinal Stenosis: Preliminary Results of a Multicenter, Randomized, Controlled Trial. (7th February 2012) - Miller, Larry E.; Block, Jon E.
Abstract : A prospective, randomized, controlled trial was conducted to compare clinical outcomes in patients treated with an investigational interspinous spacer (Superion) versus those treated with an FDA-approved spacer (X-STOP). One hundred sixty-six patients with moderate lumbar spinal stenosis (LSS) unresponsive to conservative care were treated randomly with the Superion ( n = 80 ) or X-STOP ( n = 86 ) interspinous spacer. Study subjects were followed through 6 months posttreatment. Zurich Claudication Questionnaire (ZCQ) symptom severity scores improved 30% with Superion and 25% with X-STOP (both P < 0.001 ). Similar changes were noted in ZCQ physical function with improvements of 32% with Superion and 27% with X-STOP (both P < 0.001 ). Mean ZCQ patient satisfaction score ranged from 1.7 to 2.0 in both groups at all follow-up visits. The proportion of subjects that achieved at least two of three ZCQ clinical success criteria at 6 months was 75% with Superion and 67% with X-STOP. Axial pain decreased from 55 ± 27  mm at pretreatment to 22 ± 26  mm at 6 months in the Superion group (P < 0.001 ) and from 54 ± 29  mm to 32 ± 31  mm with X-STOP (P < 0.001 ). Extremity pain decreased from 61 ± 26  mm at pretreatment to 18 ± 27  mm at 6 months in the Superion group (P < 0.001 ) and from 64 ± 26  mm to 22 ± 30  mm with X-STOP (P < 0.001 ). Back function improved from 38 ± 13 % to 21 ± 19 % with Superion (P < 0.001 ) and from 40 ± 13 % to 25 ± 16 % with X-STOP (P < 0.001 ). Preliminary results suggest that the Superion interspinous spacer and the X-STOP each effectively alleviate pain and improve back function in patients with moderate LSS who are unresponsive to conservative care.